2013
DOI: 10.1182/blood.v122.21.3311.3311
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Relapse In Adults With Acute Lymphoblastic Leukemia After Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Introduction Central nervous system (CNS) recurrence after allogeneic hematopoietic stem cell transplantation (HSCT) confers a poor prognosis in adult patients with acute lymphoblastic leukemia (ALL). Preventing CNS recurrence after HSCT remains a therapeutic challenge, and criteria for post-HSCT CNS prophylaxis have not been addressed. Our goal was to investigate the post-HSCT outcome of ALL patients and identify patient groups who may benefit from post-HSCT CNS prophylaxis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 0 publications
0
21
2
Order By: Relevance
“…While the trend has been to omit radiotherapy in pediatric patients, recent data suggest the addition of a CB in select adult ALL populations decreases rates of CNS relapse. 10 There are currently no data to guide management decisions in AYA patients regarding the use of CNS-directed therapy in patients who may be at high risk of CNS relapse post-HCT. Our study aimed to assess disease outcomes in high-risk AYA patients undergoing allo-SCT for ALL, with a focus on CNS failure and the addition of a CB to pretransplant TBI protocols.…”
Section: Discussionmentioning
confidence: 99%
“…While the trend has been to omit radiotherapy in pediatric patients, recent data suggest the addition of a CB in select adult ALL populations decreases rates of CNS relapse. 10 There are currently no data to guide management decisions in AYA patients regarding the use of CNS-directed therapy in patients who may be at high risk of CNS relapse post-HCT. Our study aimed to assess disease outcomes in high-risk AYA patients undergoing allo-SCT for ALL, with a focus on CNS failure and the addition of a CB to pretransplant TBI protocols.…”
Section: Discussionmentioning
confidence: 99%
“…17 Even with allo-HCT, further CNS therapy may be necessary to prevent these events particularly in patients with initial presentation with CNS involvement, although this is not our routine practice. 42 What is the role of newer, more potent TKIs?…”
Section: Patientmentioning
confidence: 99%
“…There are no prospective, and very limited retrospective, data regarding the role of post-transplantation CNS-directed prophylactic therapy. Wide variations in clinical practice have been reported in the literature [3,17]. The Fred Hutchinson Cancer Research Center reported a retrospective analysis from 1970 to 1980 that compared 198 patients with ALL who received (n = 127) or did not receive (n = 71) CNS ITT prophylaxis in the context of total body irradiation (TBI)-based myeloablative conditioning and allogeneic bone marrow transplantation (allo-BMT) [18].…”
Section: Cns Prophylaxis Post-allo-hctmentioning
confidence: 99%
“…The use of TBI with conditioning (P = .96), pretransplantation cranial irradiation (P = .91), and post-transplantation ITT prophylaxis (P = .33) did not confer protection from CNS relapse post-transplantation. Finally, in the largest multicenter retrospective analysis of the role of post-transplantation ITT CNS prophylaxis, which included 452 patients age 18 years who underwent allo-HCT for ALL in the contemporary era (2000 to 2011) [17]. Owing to institutional practice variations, the authors were able to compare the incidence of CNS relapse in ALL as related to the inclusion or omission of post-transplantation prophylaxis.…”
Section: Cns Prophylaxis Post-allo-hctmentioning
confidence: 99%
See 1 more Smart Citation